2008
DOI: 10.1097/aci.0b013e3283196764
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy: what have we learnt from the ‘big trials’?

Abstract: Sublingual immunotherapy represents an effective and well tolerated treatment for seasonal allergic rhinoconjunctivitis in adults. Current ongoing paediatric trials and evaluation of long-term effects in adults will further define its role in therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
(43 reference statements)
3
25
0
1
Order By: Relevance
“…Negative publication bias is also possible although less likely following the introduction of regulatory requirements to register all clinical trials on a public database. In support of the conclusions of recent meta-analyses, recent data from large multi-centre trials of SLIT for seasonal rhinitis in adults (reviewed in [24]) and in children [25,26] have provided further evidence for the efficacy of SLIT at least for grass pollen-induced SAR (Table 1). …”
Section: Sublingual Immunotherapymentioning
confidence: 62%
See 1 more Smart Citation
“…Negative publication bias is also possible although less likely following the introduction of regulatory requirements to register all clinical trials on a public database. In support of the conclusions of recent meta-analyses, recent data from large multi-centre trials of SLIT for seasonal rhinitis in adults (reviewed in [24]) and in children [25,26] have provided further evidence for the efficacy of SLIT at least for grass pollen-induced SAR (Table 1). …”
Section: Sublingual Immunotherapymentioning
confidence: 62%
“…Although four to seven pre-seasonal injections of allergoids appear to be efficacious, the optimal number of injections has yet to be defined. In the case of SLIT one study of sublingual grass tablet immunotherapy suggested that treatment should start at least 8 weeks before the season and be continued for at least 16 weeks [24]. There are only limited data on the long-term benefits of pre-seasonal immunotherapy but there is a single report of a placebo-controlled study of 3 years' treatment with SLIT which demonstrated persistent benefit for at least 1 year following cessation of immunotherapy [33].…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…Today, there are properly configured powered studies that prove that such therapy is effective and safer than SCIT. 33 Likewise, the immunologic changes associated with SCIT also have been found with SLIT. 33,34 Many different investigators have played a role in investigating this new form of therapy.…”
Section: New Science and Forms Of Allergen Immunotherapymentioning
confidence: 94%
“…33 Likewise, the immunologic changes associated with SCIT also have been found with SLIT. 33,34 Many different investigators have played a role in investigating this new form of therapy. Two important documents published on this subject include the World Allergy Organization (WAO) article entitled "Sublingual Immunotherapy: WAO Position Paper 2009" 35 and the article entitled "Recommendations for Appropriate Sublingual Immunotherapy (SLIT) Clinical Trials."…”
Section: New Science and Forms Of Allergen Immunotherapymentioning
confidence: 94%
“…ITT, intention-to-treat; QoL, quality of life; SCIT, subcutaneous immunotherapy; SLIT, sublingual immunotherapy. *With at least 100 subjects in one or more active SIT arms and at least 100 in the control arm (according to Durham, 2008). With investigating centers in more than one country.…”
Section: Discussionmentioning
confidence: 99%